Pengaruh digital leadership, management information system, dan emotional intelligence terhadap employee performance - Dewa Elmario, Rizal (Jurnal Ilmu Manajemen, 2024)
The growth of science and technology brings a sustainability revolution to a company, and leaders must be able to direct change by using technology to adapt to the era of digitalization. For this reason, the topic of this research is directed towards digitalization and technology by selecting the object Airport Administration Department PT. Angkasa Pura I Juanda Airport, Surabaya. This research analyses and tests the influence of Digital Leadership, Management Information Systems (TNDE applications), and Emotional Intelligence on Employee Performance. Quantitative research methods with primary data sources will be used in this research. The sampling technique uses a saturated sample with a population of 31 employees of the Airport Administration Department. Statistical analysis of the study used the Structural Equation Model (SEM) with Partial Least Square (PLS) with the help of smart pls version 4 software. The results of the research explain that digital leadership has a significant positive effect on employee performance, management information systems (TNDE application) has a significant positive effect on employee performance, emotional intelligence has a considerable positive impact on employee performance, and there is a simultaneous or joint influence between digital leadership, management information system (TNDE application), and emotional intelligence on Airport Administration Department employee performance.